2022
DOI: 10.1186/s40659-022-00392-4
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles synthesized using Hyssopus Officinalis L. Extract Induced oxidative stress and changes the expression of key genes involved in inflammatory and antioxidant Systems

Abstract: Background Recent advances in the synthesis of bioactive nanoparticles resulted in the discovery and introduction of new bioactive nanoparticles to the pharmaceutical industry. In this regard, this research is aimed to synthesize the zinc oxide nanoparticles (ZnO-NPs) using Hyssopus officinalis L. extract and to evaluate the safety of nanoparticles using Balb/C mice. Methods Forty male mice were divided into four groups and received 0, 50, 100, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In line with Rahimi et al (2022) and Yousef et al study (2019) [34,39], the ndings of the present study also revealed that treatment with ZnO-NPs led to decrease gene expression of SOD, GPX and CAT as well as activity of these enzymes in the kidneys. Considering that antioxidant enzymes play an important role in free radical and ROS elimination [40], so decrease in the expression and activity of antioxidant enzymes can be considered as one of the possible reasons for the increased levels of TOS and MDA in the ZnO-NPs-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…In line with Rahimi et al (2022) and Yousef et al study (2019) [34,39], the ndings of the present study also revealed that treatment with ZnO-NPs led to decrease gene expression of SOD, GPX and CAT as well as activity of these enzymes in the kidneys. Considering that antioxidant enzymes play an important role in free radical and ROS elimination [40], so decrease in the expression and activity of antioxidant enzymes can be considered as one of the possible reasons for the increased levels of TOS and MDA in the ZnO-NPs-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…Using the Debye–Scherrer equation, the average sizes of the biosynthesized UD-ZnO, MC-ZnO, and MK-ZnO NPs were determined to be 42, 45, and 41 nm, respectively, which revealed that the nanoparticles had a spherical crystal structure. Equivalent X-ray diffraction patterns were recorded in previous studies for the green synthesis of ZnO nanoparticles [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZnO NPs were seen to reduce the expression of IL-1β, IL-6, and TNF-α in a dose-dependent manner in RAW 264.7 cells. ROS causes inflammation by initiating lipid peroxidation in the phospholipid membrane [169,170]. Controlling ROS formation, therefore, helps ZnO NP anti-inflammatory activity ZnO NPs reduce the expression of pro-inflammatory genes and proteins, allowing for the treatment of inflammatory illnesses.…”
Section: Doxorubicin Hepg2 Cellsmentioning
confidence: 99%